Decay Curve Analysis of a Damped Vibration System with Multi-force Perturbations - Ismail, Ahmad Yusuf; Noerpamoengkas, Ardi; Sasongko, Sukendro Broto (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2023)
Perturbation in a system is one of the troublesome matters in dynamics, vibration, and control. It is not only changing the system behavior but also possibly causing a mechanical failure. This paper presents the effect of perturbations on the decay curve of a damped vibration system. The perturbations are varied from single to multiple forces to give novel knowledge completing previous studies. Additionally, the system properties i.e. damping and stiffness are also varied to provide more meaningful comprehensive information and, thus, can be used in further vibrational system developments. The result shows that the multiplication of perturbation force significantly changes the decay curve slope with unique characteristics. The variation of damping and stiffness also affects not only the vibration amplitude but also the system resonance.